Comparison between microendoscopic laminectomy and open posterior decompression surgery for two-level lumbar spinal stenosis: a multicenter retrospective cohort study - Hideki Nakamoto; Junya Miyahara; Hiroyuki Nakarai; So Kato; Yuki Taniguchi; Naohiro Kawamura; Akiro Higashikawa; Yujiro Takeshita; Masayoshi Fukushima; Takashi Ono; Nobuhiro Hara; Hiroki Iwai; et al. (BMC Musculoskeletal Disorders)
Abstract Background Excellent surgical outcomes of microendoscopic laminectomy (MEL) have been reported for patients with lumbar spinal canal stenosis (LSCS). However, few reports have directly compared MEL with open laminectomy for multi-level LSCS. This study conducted a comparative analysis of patient-reported outcomes (PROs) and perioperative complications in patients undergoing two-level posterior decompression for LSCS by MEL versus open laminectomy. Methods This multicenter retrospective cohort study involved prospectively registered patients who underwent two-level posterior lumbar decompression surgery for LSCS at one of eight high-volume spine centers between April 2017 and February 2020. Chart sheets were used to prospectively evaluate demographic data, including diagnosis, operative procedure, operation time, estimated blood loss, and perioperative complications. The PROs evaluated were the numerical rating scale (NRS) score for lower back pain and leg pain, 12-item Short Form Health Survey (SF-12) score, EuroQol 5-Dimension (EQ-5D) score, Oswestry Disability Index (ODI) score, and patient satisfaction with the treatment. Results Of the 882 patients enrolled, 410 underwent MEL (MEL group) and 472 underwent open decompression (open group). A total of 667 (75.6%) patients completed the 1-year follow-up. Intraoperative blood loss was significantly lower in the MEL group than in the open group. The complication rate was comparable (12.4% in MEL group, 12.5% in open group). Although the revision rate did not differ significantly, the incidence of surgical site infection (SSI) was markedly lower in the MEL group (0.0% in MEL group, 1.3% in open group). Propensity score matching was employed to compare 333 patients who underwent MEL with 333 patients who underwent open laminectomy. Intraoperative blood loss was significantly lower in the matched MEL group than in the matched open group. The incidence of SSI was markedly lower in the matched MEL group (0.0% in matched MEL group, 1.2% in matched open group). No significant differences in the preoperative and postoperative values of the PROs or patient satisfaction were observed between the two groups. Conclusions MEL required an equivalent operating time and resulted in less intraoperative blood loss compared with laminectomy in two-level procedures. The incidence of SSI was significantly lower in the MEL group.